Evaluasi nilai keindahan dan indeks kenyamanan taman kota Lumintang Denpasar - Rada, Ignasia G.M.; Utami, Ni Wayan Febriana; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019DO - 10.24843/JAL.2019.v05.i02.p02, 2019)
Evaluation of aesthetic value and humadity index of Lumintang city park Denpasar. This research is based on the needs of the people on recreation area that meets aesthetic and comfortness aspects in accordance with the standards of a city park. Aesthetic is considered as important as a means of supporting the beauty of the city and framed the landscape to soften the stiff impression of the city buildings, beside that humadity is considered important as an effort to improve the microclimate of the city so that the community more comfortable to indulge in and around the public park. This study aims to evaluate the two main aspects in Lumintang city park which meet the psychological needs of the community by using indicators of aesthetic and comfort assessment of Scenic Beauty Estimation (SBE) and Thermal Humadity Index (THI). The method was field survey with observation technique to determine the value of temperature and humidity also questionnaires technique to determine the value of SBE and the preception dan preferences of visitors. The result of data analysis showed that the value of aesthetic in Lumintang city park belong to moderate category. The lowest value located in the easthern area which wasfountain and the highest value was located in the eastern area which wasparking lot. The comfortness index showed that Lumintang city park was belong to comfort with the most comfortable area located in southern area which was a sport area (25,10). In conclusion, the environmental enhancement necessary in order to evaluate the aesthetic value and humadity index to be a better condition for the user and meet the two aspects in a green open space.